2019
DOI: 10.1194/jlr.m092510
|View full text |Cite
|
Sign up to set email alerts
|

High-saturated-fat diet-induced obesity causes hepatic interleukin-6 resistance via endoplasmic reticulum stress

Abstract: Historically, interleukin-6 (IL-6) was considered a proinflammatory cytokine contributing to the development of obesity-associated insulin resistance (1-3). However, accumulating evidence now suggests that IL-6 may contribute to the maintenance of normal systemic glucose metabolism (4-8) and that the increased circulating IL-6 concentrations during obesity may actually be an adaptive mechanism to resist obesity-associated glucose intolerance (9). One of the first reports to challenge the dogma of IL-6 as a det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 63 publications
(126 reference statements)
0
23
0
Order By: Relevance
“…We previously reported that SMP reduced total liver TAG content in these same obese rats . Since hepatic lipids are particularly important for liver health , we expanded on this past observation and analyzed fatty acid composition of several different lipid fractions. Here, we show that SMP, exercise, or the combination of the two interventions did not alter the relative amounts of saturated fatty acids in the TAG fraction in the liver (Figure A).…”
Section: Resultsmentioning
confidence: 94%
See 4 more Smart Citations
“…We previously reported that SMP reduced total liver TAG content in these same obese rats . Since hepatic lipids are particularly important for liver health , we expanded on this past observation and analyzed fatty acid composition of several different lipid fractions. Here, we show that SMP, exercise, or the combination of the two interventions did not alter the relative amounts of saturated fatty acids in the TAG fraction in the liver (Figure A).…”
Section: Resultsmentioning
confidence: 94%
“…Fat accumulation in the liver, especially saturated fatty acids, can cause ER stress . At the same time, obesity‐associated hepatic steatosis is strongly linked to inflammation .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations